Вітовтова вежа за даними сучасних фотограмметричних досліджень - Никоненко, Д.Д.; Радченко, С.Б.; Волков, А.В. (Археологія, 2017)
У статті висвітлено результати неінвазивних досліджень архітектури Вітовтової вежі. Детально наведена методика фотограмметричних обстежень археологічних пам’яток. The article presents the results of non-invasive studies of a stone tower located within the village Vesele of Beryslav Region in Kherson Oblast, near the dam of Kakhovka hydroelectric power plant (HPP) and traditionally associated with the activities of Vytautas the Great of Lithuania. This monument has never been explored archaeologically, it is in fact unknown in the scientific literature and is not mentioned in historical sources. It is known for certain only about the usage of the tower as a water-supplying one, for a nearby winery in the 19th century by Prince P.N Troubetzkoi. The importance of the research is conditioned by the preparation for the construction of the second stage of the Kakhovka HPP, and as a result, the emerging threat of destruction of the object. The method for creating a measurably accurate 3D model and for its further investigation was chosen. In fact, a digital copy of the object was created to obtain a full information about the engineering and architectural features of the Vytautas Tower. The procedure for obtaining the initial digital data consisted of aerial photography of the object and the adjacent portion of the Earth, followed by photogrammetric processing of the images. As a result of the works performed, the external and internal diameters of the structure, the height and thickness of the walls at all levels are established. The sizes of all architectural elements are defined: windows and doors apertures and apertures from fastening of wooden beams. Measurement errors do not exceed 5,0 cm. Thanks to a detailed instrumental survey of the Vytautas Tower it is established that the number of building layers of the object that are fixed from the outside does not coincide with the number of floors. The height of the tiers, the arrangement and relative position of the entrance and windows openings, the traces from the beams of the inner slabs indicate that, at four tiers, the tower had five floors. The upper tier coincides with the last floor, since it was built later in the 19th century. The location of the window openings indicates that at the time of construction, there was a priority of observation direction to the north. It is to the north from the tower where the existence of the old Tavan crossing is presumed. The established architectural parameters and features of the Vytautas Tower allow the authors to assume its mediaeval origin. However, it is obvious that conclusions about the time of its occurrence and the nature of its usage during its existence are impossible without performing archaeological research. В статье приведены результаты неинвазивных исследований каменной башни, находящейся в пределах с. Веселое Бериславского р-на Херсонской обл., близ плотины Каховской ГЭС и традиционно связываемой с деятельностью Великого князя Литовского Витовта. Данный памятник никогда не исследовался археологически, практически не известен в научной литературе и не упоминается в исторических источниках. Доподлинно известно лишь об использовании башни в XIX в. князем П.Н. Трубецким в качестве водонапорной, для находящегося поблизости винодельного хозяйства. Актуальность проведенных исследований обусловлена подготовкой к строительству второй очереди Каховской ГЭС, и как следствие — возникшей угрозой уничтожения объекта. Для получения полной информации про инженерные и архитектурные особенности башни Витовта выбран метод создания измерительно точной 3D-модели и ее дальнейшего исследования. Фактически была создана цифровая копия строения. Процедура получения исходных цифровых данных состояла из аэрофотосъемки объекта и прилегающего участка Земли, с последующей фотограмметрической обработкой снимков. В результате проведенных работ установлены внешние и внутренние диаметры строения, высота и толщина стен на всех уровнях. Определены размеры всех архитектурных элементов — оконных и дверных проемов, отверстий от крепления деревянных балок. Погрешность измерений расстояний не превышает 5,0 см. Благодаря детальному инструментальному обследованию башни Витовта установлено, что количество строительных ярусов объекта, которые фиксируются с наружной стороны не совпадает с количеством этажей. Высота ярусов, обустройство и взаимное расположение входных и оконных отверстий, следы от балок внутренних перекрытий указывают на то, что при четырех ярусах башня имела пять этажей. Верхний ярус совпадает с последним этажом, так как был надстроен позже в XIX в. Расположение оконных проемов свидетельствует о наличии на момент строительства приоритетного для наблюдения направления на север. Именно на север от башни предполагается существование давней Таванской переправы. Установленные архитектурные параметры и особенности башни Витовта позволяют предположить ее средневековое происхождение. Однако, очевидно, что выводы о времени ее возникновения и характере использования на протяжении существования невозможны без проведения археологических исследований.